Hegel’s Notion of Entäußerung as Active Justice - Bubbio, Paolo Diego (Journal for the academic study of religion, 2024)
This article investigates the connection between Hegel’s notion of kenosis and his account of justice, exploring the relevance of this connection in assessing Hegel’s political theology and its lasting influence. The inquiry approaches the kenotic aspect of Hegel’s thought by focusing on the notion of Entäußerung as externalisation, aiming to highlight its active aspect. The article argues that within the dialectical mediation between interiorisation and externalisation, Hegel’s conception of justice is functionally structured as a form of Entäußerung. It surveys some of the most notable responses offered in recent decades to the question whether Hegel can contribute to the dismantling of inequality and the affirmation of justice. Subsequently, it argues that an interpretation of justice that takes into consideration the dual movement of interiorisation and externalisation enables the recollection and transformation of memories of struggles in the pursuit of justice. Lastly, the article explores the advantages that interpreting justice as Entäußerung offers in terms of social change and progress compared to alternative perspectives, and suggests that such an interpretation can provide a meaningful contribution to a new political theology of the oppressed.